2016
DOI: 10.1093/mnras/stw2353
|View full text |Cite
|
Sign up to set email alerts
|

PSR B0329+54: substructure in the scatter-broadened image discovered with RadioAstron on baselines up to 330 000 km

Abstract: We have resolved the scatter-broadened image of PSR B0329+54 and detected substructure within it. These results are not influenced by any extended structure of a source but instead are directly attributed to the interstellar medium. We obtained these results at 324 MHz with the ground-space interferometer RadioAstron which included the space radio telescope (SRT), ground-based Westerbork Synthesis Radio Telescope and 64-m Kalyazin Radio Telescope on baseline projections up to 330,000 km in 2013 November 22 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…We note a possible excess of fractional detections at the longest RadioAstron projected baselines at 18 cm in comparison to the 6 cm results of about the same sensitivity. This can be an indication of the scattering sub-structure originally discovered in RadioAstron pulsar observations Popov et al, 2017) and later confirmed by the ground-based observations of Sgr A* (Gwinn et al, 2014;Johnson et al, 2018). See also the analyses of RadioAstron data for the quasars 3C 273 (Johnson et al, 2016) and B 0529+483 (Pilipenko et al, 2018).…”
Section: Space Vlbi Data Analysis and Detection Resultssupporting
confidence: 64%
“…We note a possible excess of fractional detections at the longest RadioAstron projected baselines at 18 cm in comparison to the 6 cm results of about the same sensitivity. This can be an indication of the scattering sub-structure originally discovered in RadioAstron pulsar observations Popov et al, 2017) and later confirmed by the ground-based observations of Sgr A* (Gwinn et al, 2014;Johnson et al, 2018). See also the analyses of RadioAstron data for the quasars 3C 273 (Johnson et al, 2016) and B 0529+483 (Pilipenko et al, 2018).…”
Section: Space Vlbi Data Analysis and Detection Resultssupporting
confidence: 64%
“…Thus, we estimated the scintillation time, t scint = 115s, as the 1/e half width of this curve. The scintillation time is in approximate agreement with the value of t scint = 110 − 112s determined earlier for this pulsar from single-dish autocorrelation spectra (Popov et al 2017). We find the same characteristic of the SN amplitude decreasing with increasing magnitude of time lag, ∆t, approximately as a Gaussian for each pulsar in our sample and list our values for t scint in Table 1.…”
Section: The Unresolved Spikesupporting
confidence: 89%
“…Our pulsars B0329+54, B0823+26, B0834+06 and B1933+16 are all undergoing isotropic scattering. Their galactic coordinates and the relative distances of their scattering screens (see , Table 1) indicate that for the first three pulsars the screens are approximately associated with the Local Arm in our Galaxy and for B1933+16 with the Carina Sagittarius Arm (see also , Fadeev et al (2018); Popov et al (2017)). Despite the large range of their distances, D, dispersion measures, DM , scintillation times, t scint , scattering times, τ sc , (AT-CD)×(HO-CD) CCF RR 5.8-7.5, 9.3 1.1(1) 10.0(2) 0.03 0.05 (AT-CD)×(AT-HO) CCF RR 5.…”
Section: Discussionmentioning
confidence: 90%
“…Studies of pulsars revealed a new effects of radio emission scattering on the interstellar medium. High angular resolution of space-ground interferometer resolved the substructure in the scattering disk [8,9]. Later, driven by the Radioastron revealed scattering disk substructure, the same effect was observed for the Galactic center [10].…”
Section: Radioastron Missionmentioning
confidence: 66%